2010
DOI: 10.1002/ppul.21386
|View full text |Cite
|
Sign up to set email alerts
|

Lung function and overweight in school aged children after early childhood wheezing

Abstract: Background and purpose Recently, obesity has been connected with wheezing, asthma and reduced lung function. Most previous studies have been cross‐sectional. The aim of the present follow‐up study was to evaluate the association of preceding or current overweight or obesity with lung function at early and late school age after early childhood wheezing. Material and methods From the 100 children hospitalized for infection associated wheezing at <24 months of age, 83 attended the control visit at 4.0 years, 82 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
1
11
0
1
Order By: Relevance
“…Second, no association was found between previous or current overweight or obesity and asthma or BHR at 7.2 or 12.3 years of age. However, overweight at 7.2 and 12.3 years of age was associated with decreased FEV 1 /FVC (forced vital capacity), and overweight and obesity at 7.3 years of age were predictive for decreased FEV 1 /FVC at 12.3 years of age in the same cohort, as published recently (25). And third, preliminary evidence was found that obesity (BMI >2.0 SD corresponding BMI >30 in young adults) may decrease the risk of allergy at late school age.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Second, no association was found between previous or current overweight or obesity and asthma or BHR at 7.2 or 12.3 years of age. However, overweight at 7.2 and 12.3 years of age was associated with decreased FEV 1 /FVC (forced vital capacity), and overweight and obesity at 7.3 years of age were predictive for decreased FEV 1 /FVC at 12.3 years of age in the same cohort, as published recently (25). And third, preliminary evidence was found that obesity (BMI >2.0 SD corresponding BMI >30 in young adults) may decrease the risk of allergy at late school age.…”
Section: Discussionsupporting
confidence: 80%
“…In conclusion, no evidence was found for an association between previous or current overweight and asthma in former bronchiolitis patients at school age, although overweight in the same cohort was associated with reduced lung function (25). Obesity may even decrease the risk of allergy and atopic sensitization at late school age.…”
Section: Discussionmentioning
confidence: 80%
“…Interestingly, no overweight/obese patient in the present study had any characteristics of metabolic syndrome. In contrast, obesity in CF appears to exert a positive effect on lung function contrary to what is known about its role in non‐CF subjects . Nevertheless, according to certain reports, this positive association between NS and pulmonary function is limited to adult BMI below 23 kg/m 2 ; therefore counseling for weight management is advisable for this patient group as well .…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, obesity in CF appears to exert a positive effect on lung function contrary to what is known about its role in non-CF subjects. 36 Nevertheless, according to certain reports, this positive association between NS and pulmonary function is limited to adult BMI below 23 kg/m 2 ; therefore counseling for weight management is advisable for this patient group as well. 17 The question whether overweight or obesity is also associated with improved clinical outcome is one that warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that overweight and obesity may increase asthma risk in children at school age (3,22). Excessive weight gain seems to be associated with asthma symptoms, treatments and diagnoses (22), and even with decreased lung function (23), but not with bronchial hyper‐responsiveness (22). We found some evidence that an excessive weight gain assessed by WFL, in line with three other studies applying length‐related weight gains for infants (4,5,9), increases the risk of wheezing in early years.…”
Section: Discussionmentioning
confidence: 99%